Country-of-origin and industry FDI agglomeration of foreign investors in an emerging economy - Tan, Danchi; Meyer, Klaus E (Journal of International Business Studies, 2011)
Foreign investors access local knowledge by co-locating with other foreign direct investment (FDI) firms. However, different aspects of local knowledge can be obtained from different local businesses. Thus some foreign investors co-locate with FDI firms from the same country of origin, while others co-locate with foreign industry peers. We argue that, relative to industry FDI agglomeration, country-of-origin agglomeration provides an effective channel for the sharing of sensitive and tacit knowledge about local business environments. Therefore foreign investors in need of such local knowledge are more likely to locate in country-of-origin agglomerations. Empirical evidence based on FDI in Vietnam indicates that foreign investors who perceive local institutions as particularly weak, and those with a high degree of outsidership in the local environment, are more likely to seek country-of-origin agglomerations than industry FDI agglomerations.